INCLUSIVENESS IN SHAPING THE LANDSCAPE FOR AN EQUAL EDUCATIONAL ENVIRONMENT - Malik, Tetiana; Pashchenko, Наnna; Vitt, Lilia (Theory and practice of design, 2024)
Purpose. Objective To assess and clarify the crucial role of inclusiveness in the formation of a fair educational environment. It delves into the fundamental notion that education should be a universal right available to all, regardless of their background, ability or personality. Methodology. The article uses general scientific research methods: analysis, synthesis, comparison, generalization. To study the state of inclusiveness in the landscape design of the territories of higher education institutions, the methods of content analysis and expert evaluations were used. A methodology for improving the accessibility and inclusiveness of the campus landscape is outlined. Results of the study reveal the dominant inconvenience of the current state of the territories of educational institutions in Ukraine. The existing structures of the landscape area become a challenge for people with disabilities, despite the mandatory requirement for inclusive planning. The idea of inclusion, which arose as a result of the awareness of the value of human diversity and differences between people, excludes any discrimination and reflects one of the main features of a democratic society: all people are valuable members of society and have equal rights, in particular to receive education, despite the peculiarities of their psychophysical development This discrepancy highlights the urgent need for a comprehensive reform of the design and planning of educational spaces. Scientific novelty of the article consists in the justification and necessity of taking into account inclusive principles in the design of the territories of colleges and institutions of higher education, and consists in the study of specific aspects of landscape design, as well as the use of new technologies and innovative approaches. A significant innovation in the campus landscape regarding inclusiveness in creating an equitable educational environment is the implementation of the principles of universal design for learning, which focuses on designing educational spaces, materials, and practices to meet the needs of a wide range of students, including those with disabilities. Such an article can be useful for the formation of an effective university policy and program on inclusiveness.